Marketing Mix on Consumer Purchase Decisions on SPHP Rice At Irian Supermarket Medan City - Ocdy Amelia; Debora (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The achievement of retail goals is marked by the number of consumers who make purchases or transactions on products so that the need for these products is a direction of consumer behavior. SPHP rice products are not placed in a specific place, making it difficult for consumers to find or choose products. The price of SPHP rice is higher than similar products from competitors in the same location. The promotion of SPHP rice in the Irian product brochure does not match the product on the shelf. The location of Irian is relatively narrow where parking is limited and Irian is at an intersection that is not clearly visible from the main road. The purpose of the study was to determine the Product, price, promotion and location of the consumer purchasing decision of SPHP rice at Irian Supermarket Jl. Hm. Joni. The research method used in this study is a quantitative approach that is associative. The population of the study was all consumers who shopped for SPHP rice at Irian Supermarket for 1 month as many as 123 people, using the slovin formula, a sample of 94 people was determined. The results of the study found a significant influence of price obtained a t-value of 2.743, while the t-table value was 1.98698 with a sig value = 0.007 <0.05). Significant influence of product obtained a t-value of 2.304, while the t-table value was 1.98698 with a sig value = 0.002 >0.05). Significant influence of promotion obtained a t-value of 6.662, while the t-table value was 1.98698 with a sig value = 0.000 <0.05). Significant influence of place obtained a t-value of 2.249, while the t-table value was 1.98698 with a sig value = 0.004 <0.05). F count value at level α = 0.05 is 19.995 (F0.05 = 2.47), and significance value of 0.000 means significance value (0.000) <0.05. Conclusion of research partially and simultaneously Product, price, promotion and location have a significant effect on consumer purchasing decisions of SPHP rice at Irian Supermarket Jl. Hm. Joni.